Creationism and evolutionism from the model of levels of analysis perspective – with reference to fragments of writings by Piotr Lenartowicz SJ - Bylica, Piotr (Studia Ecologiae et Bioethicae, 2019)
The model of levels of analysis (MLA) distinguishes among five types of descriptive statements on reality depending on their level of empirical testability. The aim of this article is to use the MLA in categorising variants of creationism and evolutionism and the statements these contain. This will allow one to evaluate how the distinguished variants fit in in terms of the attempts at bringing together science and religion and the problem of scientific character of respective statements found within creationism or evolutionism. The article makes a number of references to Piotr Lenartowicz’s claims, whose opinions are considered as important in the debate on the character of the described variants. In terms of Lenartowicz’s views, the use of MLA will allow distinguishing between valid claims regarding the philosophical and social factors in science and the hardly tenable ones, when one takes into account what modern philosophy of science has to say on the relations between observation, theory and philosophical factors. In particular, MLA makes it easier to notice that the philosophical and theological views of theistic character that supposedly follow from an unbiased observation of the world are, in fact, used as assumptions that influence what one views as facts.